Balanced time perspective as a facilitator of immigrants' psychological adaptation: A study among Ukrainian immigrants in Poland. (December 2021) - Marczak, Michalina; Sorokowski, Piotr; Sobol, Małgorzata
The perception of time plays a fundamental role in the organisation of basic psychological processes, and as such may also influence migrants' psychological wellbeing. This paper investigates the relationship between the perception of time and immigrants' psychological adaptation (i.e., affective aspects of migration) based on a sample of 238 Ukrainians residing in Poland. To assess time perception, we drew primarily from time perspective theory, which defines time perspective as a measure of the degree to which individuals non-consciously construe the past, the present, and the future. Psychological adaptation was assessed, focusing on participants' basic psychological needs satisfaction, their satisfaction with life, and their psychological condition. We observed a relatively strong negative relationship between negative past and fatalistic present time perspectives and psychological adaptation. Additionally, we found that a more balanced and less negative temporal profile was related to significantly better psychological adaptation of immigrants. We discuss these results in light of the cultural validity of time perspective theory, the destructive impact of negative time perspective on migrants' psychological wellbeing, and the potential applications of time perspective-based therapy in integration interventions for immigrants.